PATTERN OF NAZHIR WAKF DEVELOPMENT IN THE CITY OF BANDA ACEH - Husni Abdul Jalil; Bukhari Ali; Al Muzammir Saputra (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2022)
ABSTRACT Based on waqf regulations in Indonesia, Nazhir waqf is entitled to receive guidance from the government (central Ministry of Religion, Regional Office of the Ministry of Religion, Regency/City Ministry of Religion and KUA) and the Indonesian Waqf Board. However, the waqf regulations in Indonesia do not regulate the pattern of development. This study examines how the pattern of coaching Nazhir in the city of Banda Aceh. The method used in this research is a qualitative method that is a field study or empirical and the focus of the study is the role of the government in fostering Nazhir in the city of Banda Aceh. The results of the study show that the pattern of Nazhir's development in the city of Banda Aceh is a formal and informal pattern. Formal patterns such as seminars, workshops and training. Meanwhile, informal patterns such as at the time of sermons, religious lectures, at the momentum of the handover of Nazhir's decree, the participants were very limited and attended by participants other than Nazhir waqf.